Comparative Study on Performance of Islamic Banks and Conventional Banks: Evidence from Oman - Bilal, Zaroug Osman; Durrah, Omar Mohammad; Atiya, Tariq Mohamed (International Journal of Economics and Financial Issues, 2016)
This research aims to examine and compare the performance for Islamic banks (IBs) and conventional Banks (CB) in Oman during 2013-2015. Financial ratio analyses are employed to measure profitability, solvency and capital adequacy of seven conventional banks and two Islamic bans. IndependenSamples t T- Test was used to determine the whether there is a difference in the performance for IBs and CB. The finding of the research establishes that conventional banks are more profitable and significantly different from Islamic banks in terms of return on assets (ROE), return on equity (ROE) and Net profit margin (NPM). While, Islamic banks were performing better in term of efficiency ratio (EFR), debt to assets ratio (DAR). debt to equity ratio (DER) and credit to deposits ratio (TCTD) .The difference is statistical significant. Keywords: Islamic Banks, Conventional banks, Performance, Oman JEL Classifications: G35, G38, M41